In-situ synchrotron X-ray analysis of metal Additive Manufacturing: Current state, opportunities and challenges - Ioannidou, Chrysoula; König, Hans Henrik; Semjatov, Nick; Ackelid, Ulf; Staron, Peter; Körner, Carolin; Hedström, Peter; Lindwall, Greta (Materials and Design, 2022)
Additive Manufacturing (AM) is becoming an important technology for manufacturing of metallic materials. Laser-Powder Bed Fusion (L-PBF), Electron beam-Powder Bed Fusion (E-PBF) and Directed Energy Deposition (DED) have attracted significant interest from both the scientific community and the industry since these technologies offer great manufacturing opportunities for niche applications and complex geometries. Understanding the physics behind the complex and dynamic phenomena occurring during these processes is essential for overcoming the barriers that constrain the metal AM development. In-situ synchrotron X-ray characterization is suitable for investigating the microstructure evolution during processing and provides new profound insights. Here, we provide an overview of the research on metal PBF and DED using in-situ synchrotron X-ray imaging, diffraction and small-angle scattering, highlighting the state of the art, the instrumentation, the challenges and the gaps in knowledge that need to be filled. We aim at presenting a scientific roadmap for in-situ synchrotron analysis of metal PBF and DED where future challenges in instrumentation such as the development of experimental stations, sample environments and detectors as well as the need for further application oriented research are included.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Directed energy deposition; In-situ studies; Metal additive manufacturing; Powder bed fusion; Synchrotron X-ray characterization